Evaluasi Tuntutan Kognitif pada Departemen SDM dan Umum di PT. ABC dengan Metode NASA-TLX - Steffi Eka Kristanti Sutikno; Adhie Tri Wahyudi; Muhammad Ave Sina (Tekinfo: Jurnal Ilmiah Teknik Industri dan Informasi, 2025)
Employee performance and well-being may be impacted by a high-pressure work environment's increased cognitive burden. For managerial solutions to be more focused, it is necessary to determine the underlying reasons of this condition. The purpose of this study is to determine the predominant factors and evaluate the cognitive workload levels of employees at PT. ABC's HR and General Affairs Department using the NASA-TLX method. Observation, NASA-TLX questionnaire distribution, and SPSS data processing (descriptive analysis, normality test, and Independent Samples t-Test) are the techniques employed. Five of the twelve respondents fell into the category of very high cognitive load, six into the category of high, and one into the category of moderately high; job performance factors, especially those pertaining to meeting KPI report targets, appeared as the predominant factor. The test findings indicate that the data distribution is normal. There is not a significant distinction in the cognitive load levels of structural and non-structural employees, according to the test findings, which display a normal data distribution. In order to lessen work-related stress, recommendations include establishing more flexible working hours and offering support facilities (such pantries). These results help businesses create more efficient cognitive load management plans and create avenues for additional research using various analytical techniques.